1 Peter: an introduction and study guide : reading against the grain - Schüssler Fiorenza, Elisabeth (T & T Clark study guides to the New Testament, 2017)
Introduction : How do you approach 1 Peter? -- Rhetorical analysis of 1 Peter -- Making our Jewish ancestors audible -- Reconstructing the arguments of the subordinated -- Exploring the meaning of 1 Peter for today -- Instead of a conclusion